I don’t care why you do it, just don’t! Reactions to negative and positive organizational deviance partly depend on the desire for tightness of prevention-focused employees - Mula, Silvana; Pierro, Antonio (Frontiers in Psychology, 2022)
Tightness-Looseness (T-L) at the individual-level has only begun to receive attention from researchers. Specifically in the organizational context, this is a so far unexplored construct. The study offers first insights into the mechanisms that can trigger individuals’ desire for tightness and the consequences it can have on organizational behaviors. We, therefore, investigated the mediating role of the desire for tightness on the relationship between work regulatory prevention focus and emotional responses to both negative and positive (i.e., pro-social) deviant organizational behaviors. We tested our prediction through a mediational model with a sample of 788 Italian employees (58.6% females, Mage = 35.09). Our findings supported the hypothesized model showing that regardless of the motivation underpinning the norm-violating behavior, employees with a prevention focus are more desirous of tightness and exhibit hostile reactions towards deviance. Given its importance in understanding employees’ behaviors and intentions, which inevitably reflect on the organization's functionality, the impact of the T-L individual-level dimension in organizations is undoubtedly worthy of deeper investigation.